DNASE-MEDIATED DISSOLUTION OF NEUTROPHIL EXTRACELLULAR TRAPS ACCELERATES IN VITRO THROMBIN GENERATION KINETICS IN TRAUMA PATIENTS. Issue 3 (8th September 2022) - Goswami, Julie; MacArthur, Taleen A.; Mahony, Cillian; Kizhakkedathu, Jayachandran N.; Vappala, Sreeparna; Smith, Stephanie; Morrissey, James H.; Spears, Grant M.; Bailey, Kent R.; Dong, Jing-Fei; Kozar, Rosemary A.; Hall, Nathan; et al.
ABSTRACT: Introduction: Neutrophil extracellular traps (NETs) trigger thrombin generation. We aimed to characterize the effects of deoxyribonuclease (DNAse) on NET components (cell-free DNA [cfDNA] and histones) and thrombin generation after trauma. Methods: Citrated plasma samples were collected from trauma patients and healthy volunteers. Thrombin generation (calibrated automated thrombogram) was measured as lag time (LT, in minutes), peak height (in nM), and time to peak thrombin generation (in minutes). Citrullinated histone 3 (CitH3) and 4 (CitH4) were measured by enzyme-linked immunosorbent assay; cfDNA by PicoGreen (all in nanograms per milliliter). Samples analyzed +/− DNAse (1, 000 U/mL). Results expressed as median and quartiles [Q1, Q3], Wilcoxon testing, P < 0.05 significant. Results: We enrolled 46 patients (age, 48 [31, 67] years; 67% male) and 21 volunteers (age, 45 [28, 53] years; 43% male). Deoxyribonuclease treatment of trauma plasma led to shorter LT (3.11 [2.67, 3.52] min; 2.93 [2.67, 3.19] min), shorter time to peak thrombin generation (6.00 [5.30, 6.67] min; 5.48 [5.00, 6.00] min), greater peak height (273.7 [230.7, 300.5] nM; 288.7 [257.6, 319.2] nM), decreased cfDNA (576.9 [503.3, 803.1] ng/mL; 456.0 [393.5, 626.7] ng/mL), decreased CitH3 (4.54 [2.23, 10.01] ng/mL; 3.59 [1.93, 7.98] ng/mL), and increased H4 (1.30 [0.64, 6.36] ng/mL; 1.75 [0.83, 9.67] ng/mL), all P < 0.001. The effect of DNAse was greater on trauma patients as compared with volunteers for LT (ΔLT, −0.21 vs. −0.02 min, P = 0.007), cfDNA (ΔcfDNA −133.4 vs. −84.9 ng/mL, P < 0.001), and CitH3 (ΔCitH3, –0.65 vs. −0.11 ng/mL, P = 0.004). Conclusion: Deoxyribonuclease treatment accelerates thrombin generation kinetics in trauma patient samples as compared with healthy volunteers. These findings suggest that NETs may contribute to the hypercoagulable state observed in trauma patients.